Alcohol Septal Ablation in Obstructive Hypertrophic Cardiomyopathy: Four Years of Experience at a Reference Center - Fiarresga, A (2014)
INTRODUCTION: We describe our center's initial experience with alcohol septal ablation (ASA) for the treatment of obstructive hypertrophic cardiomyopathy. The procedure, its indications, results and clinical outcomes will be addressed, as will its current position compared to surgical myectomy. OBJECTIVE: To assess the results of ASA in all patients treated in the first four years of activity at our center. METHODS: We retrospectively studied all consecutive and unselected patients treated by ASA between January 2009 and February 2013. RESULTS: In the first four years of experience 40 patients were treated in our center. In three patients (7.5%) the intervention was repeated. Procedural success was 84%. Minor complications occurred in 7.5%. Two patients received a permanent pacemaker for atrioventricular block (6% of those without previous pacemaker). The major complication rate was 5%. There were no in-hospital deaths; during clinical follow-up (22 ± 14 months) cardiovascular mortality was 2.5% and overall mortality was 5%. DISCUSSION AND CONCLUSION: The results presented reflect the initial experience of our center with ASA. The success rate was high and in line with published results, but with room to improve with better patient selection. ASA was shown to be safe, with a low complication rate and no procedure-related mortality. Our experience confirms ASA as a percutaneous alternative to myectomy for the treatment of symptomatic patients with obstructive hypertrophic cardiomyopathy refractory to medical treatment.